Acne as a public health problem (Italian Journal of Public Health, 2010)
Although acne is the most common skin disorder, epidemiological data on this condition are scarce. The social and economic effects of acne are mostly related to the high prevalence of this pathology, so much so that we can consider acne as a public health problem. Our proposal is to realize a computerized case sheet for each acne sufferer based on a minimum data set. This should include: patient’s age, sex, clinical form of acne and grade of severity. This information should then be introduced into a database management system. Examining the data collected we hope to contribute to the efficient use of health care resources and to improve management of public health problems highlighted in prior epidemiological investigations.
Keywords: Acne; epidemiology; treatment costs; quality of life